Leaks, Hacks, and Scandals: Arab Culture in the Digital Age, written by Tarek El-Ariss. - Colla, Elliott (Journal of Arabic Literature, 2024)
Tarek El-Ariss's book, "Leaks, Hacks, and Scandals: Arab Culture in the Digital Age," is a valuable resource for understanding contemporary writing practices in the Arab world. It examines the impact of digital platforms on Arab literature, including blogging and social media, and explores the legal and social consequences of these cultural developments. The book draws on various disciplines, such as digital media studies, affect studies, and gender and sexuality studies, to provide a comprehensive analysis. Additionally, the text discusses Joseph Geha's novel "Lebanese Blonde," praising its unique perspective on the Lebanese Civil War and its experimental narrative style.